Library Management in Increasing Reading Interest of Female Santri Dayah of Muslimat Samalanga - Barrulwaliddin; Yusnadi; Ishak; Raudhatul Juniati; Tuhfatul Athal (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
This research is motivated by the management of library management, development of book collections, supporting and inhibiting factors as well as an increase in students' reading interest. This study aims to determine the role of libraries, namely librarian, collection, management management and increase the interest in reading fondness for Dayah Putri Muslimat Samalanga santri, Bireuen Aceh Regency. The purpose of this study was to identify and describe the planning, procurement, use, inventory, deletion, inhibiting and supporting factors of libraries in Dayah Putri Muslimat Samalanga. This research is a qualitative research using descriptive method. Data collection was carried out by interview, observation, and documentation study. The data analysis technique was carried out through descriptive interpretation, data validity testing, participation extension, and auditing. Library planning is carried out by musyarawah, organizing is carried out by selecting and mutually agreed upon, implementation is carried out in accordance with the plan and according to their respective duties and supervision is carried out every day such as supervision of circulation and cleaning services, tidiness and discipline. Collection development is carried out by deliberation and submissions from visitors, the supporting factor is the routine allocation of funds from the dayah for the development of the Dayah Putri Muslimat library and librarians who equate it, the inhibiting factor is that the available librarians are not graduates from their fields.